The Effect of Financial Behavior on the Use of PayLater with Gender Moderation on Employees of PT Ihara Manufacturing Indonesia - Melawati Purwasih,; Uus Mohammad Darul Fadli,; Ery Rosmawati, (Research in Management of Technology and Business, 2025)
The development of financial technology in Indonesia has brought significant changes in financial services. One of the increasingly popular fintech innovations is PayLater, an online non-credit card loan service with easy to pay of instalments at a later date. Understanding the extent of PayLater usage on individual financial conditions, especially in the context of the financial behavior of employees, and how demographic factors such as gender can shape the pattern of PayLater service usage. This research use qualitive methodology and conducted at PT Ihara Manufacturing Indonesia with 343 employees as the population. The research sample consisted of 80 PayLater user respondents selected using the Hair et al. (2014) formula, using the largest number of indicators, then multiplied by ten were analyzed. Primary data were collected through distributing questionnaires using Google Form. Measurements were made using a differential scale that has a value range from 1 (lowest) to 5 (highest). The data analysis mechanism applied was Structural Equation Modeling (SEM) using the Partial Least Square (PLS) approach, executed with the help of SmartPLS 4 software. Finding from the study demonstrate a sifnificant role for financial behavior in enhancing the use of PayLater. Futhermore, gender became a moderating factor in the relationship of financial behavior and the use of PayLater, where gender differences influence decisions and patterns of use of the service. This study contributes to enriching the literature related to financial behavior in the digital era and provides practical insights for companies in supporting employees to manage personal finances wisely.